Effectiveness Cream and Ointment of Spirulina platensis extract against amount of Fibroblas and Wound Area: Study on white rats whose skin is incised - Bimby Irenesia; Renni Yuniarti; Endang Mahati (Indonesian Journal of Environmental Management and Sustainability, 2020)
Spirulina platensishas been well-known as an abundant protein and phycocyanin. Spirulina platensis has the effect of anti-inflammatory, so it is widely used to apply cosmetics and biomedicine in the healing process of wounds. To prove that the administration of an extract ofSpirulina platensiscan increase the number of fibroblasts and accelerate the wound healing process in Wistar rats with an incision on their skin. This study used a randomizedpost-test only control group design. The skins of thirty (30) male Wistar rats were incised. This treatment was divided into 4 groups, namely the group that received the 0,1% cream (X1) of S.platensisextract, and the group that was administered with the 0,1% ointment (X2) of S.platensis extract; the negative control group was only treated by a saline solution (C1), and the positive control group was with the administration of Gentamycin 0,1% ointment (C2). The total numbers of fibroblasts were examined on day 14 and calculated using the method of tissue biopsy and hematoxylin-eosin (HE) staining. The wound was checked after 14-day Data analysis was performed with a one-wayANOVA test and was continued by Post Hoc Test LSD. The total numbers of fibroblasts on day 14 from the group of XI, X2, C1, and C2 were 15.00; 17,50; 3,83, 10,33 with p<0.001. The average size of the wounds on day 14 from the groups of X1, X2, C1, and C2 was 551,78; 435,76; 1795,95; 1193,57 with p<0.001, respectively. PostHoc Testresults on the total number of fibroblasts and extensive wound area showed significant differences between them. Administration of the 0.1% ointment of Spirulina platensisextract believed to potentially increasing the number of fibroblasts and accelerate the process of wound healing.